Multimodality and dubbing in video games: A research approach - Mejías-Climent, Laura (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
This article discusses a new taxonomy of dubbing synchronies in the Spanish localized version of the video game Batman: Arkham Knight. To do so, the concept of the video game is first reviewed as the most sophisticated example of audiovisual text in terms of its multimodal nature. The article also describes how the message is conveyed through the different communication channels that form a part of its semiotic structure. Next, the research approach proposal is presented, based on the multimodal configuration of video games: game situations will be the unit of analysis used in this approach, since they are a basic unit with which to organize the content of a game and they distinguish video games as a unique type of audiovisual text. These game situations are used to analyse the specific features of dubbing and types of synchrony. Finally, some results are offered to confirm that the taxonomy of dubbing in video games discussed here applies to this particular case.